Islamic Education and the Development of an Entrepreneurial-Minded Generation through a Sociocultural Approach - Sulisno, Sarwadi (Peneliti.net, 2025)
In the quickly changing age of globalization and digitization, Islamic education faces several obstacles. A sociocultural approach is required to merge local culture, entrepreneurship, and religious beliefs in order to produce a generation of exceptional individuals who are globally competitive. Islamic education faces significant challenges in the rapidly evolving age of globalization and digitization. A sociocultural approach is necessary for a great generation that is globally competitive in order to integrate local culture, entrepreneurship, and religious convictions. This article examines how human resources (HR) can be developed through Islamic education with a sociocultural foundation to produce an independent, innovative, and enterprising generation. This study examines the suitability of Islamic education in addressing swift social, cultural, and technological changes using a qualitative methodology based on literature reviews. The sociocultural approach in Islamic education highlights how important it is to contextualize Islamic values through entrepreneurship and integration with local culture. By using this approach, students are not only transformed into religious individuals but also become change agents capable of overcoming the challenges presented by globalization.